Communicating and Disagreeing with Distinct Concepts: A Defense of Semantic Internalism. Issue 4 (4th August 2019) - Valente, Matheus
Abstract: I suggest a solution to a conflict between semantic internalism – according to which the concepts one expresses are determined by one's use of representations – and publicity – according to which, if two subjects successfully communicate or are in genuine agreement, then they entertain thoughts constituted by the same concepts. My solution rests on the thesis that there can be successful communication and genuine agreement between thinkers employing distinct concepts as long as there is a certain relation (of conceptually guaranteed sameness of extension) between them. In section 2, I motivate semantic internalism and show how it conflicts with publicity. In section 3, I carve the logical space of possible solutions to the conflict into liberal and conservative solutions. Section 4 assesses Wikforss's conservative solution to Burge's arthritis thought‐experiment and concludes that it fails for more than one reason. Section 5 introduces a new case study involving a deferential concept. This case serves as the backdrop for my positive account offered in section 6. The conclusion of the article is preceded by a comparison of my view with another recently proposed by Recanati (section 7) and some replies to possible objections (section 8).